Pembuatan Video Panduan Layanan Perpustakaan di Perpustakaan Universitas Dharma Andalas Padang - Desmal, Susmita; Rahmah, Elva (Ilmu Informasi Perpustakaan dan Kearsipan, 2016)
This paper discusses the making of the video guide library services at the Andalas University Library Dharma. This paper aims to describe the making of video services at the library of the University Library guide Dharma Andalas Padang.The method used in this paper is a qualitative method. Data were collected through direct observation, interviews with the head of Dharma Andalas University Library, librarians and literature. Based on analyzing the data, it can be concluded that the steps in the manufacture of video services guide as follows. First, pre-production is the early stages before the implementation of video production that consists of the search and the discovery of the idea, synopsis, treatment, storyboard, script shotting, production planning and production preparation. Second, the production to realize all the steps in the pre-production stage. Third, post-production of the final stages in the production of the video before the video is ready to be served or distributed.Keyword: Video, library, guide.